The naturalist and his 'beautiful islands' : Charles Morris Woodford in the Western Pacific - Lawrence, David (David Russell) (ANU Press, 2014)
"In January 1890 the account of three visits to the Solomon Islands made between 1886 and 1889 by the young English naturalist, Charles Morris Woodford, was published in London, to some critical acclaim, by George Philip and Sons. With a typical late-Victorian eye for romance in the exotic, and an appeal to the vogue for tales of adventure and daring, his publisher called the book A Naturalist Among the Head-hunters (Woodford 1890b). In that same year it was published in three editions, one in London, one in Melbourne, and one in New York. For a young traveller's account and first published book, it is well written, sympathetic to the social and economic conditions of the Solomon Islanders of that time and, even now, is very evocative for anyone familiar with the islands and the people. Publication of the book further emphasised the practical value of scientific observation from the field. Arguments about the relationship between observations made in the field and the scientific theorising made in the study and the museum were endemic in the world of 19th century natural history (Driver 1998: 24). Knowledge from the field was not always to be trusted. For the author, the authority of his exploration depended substantially on the writing of a well-accepted narrative of travel"--Introduction